New Technology for Teaching and Learning Science for Educators and Students as Support for the Independent Curriculum: Systematic Literature Review - Apit Fathurohman; Lintang Auliya Kurdiati; Syarifuddin; Esti Susiloningsih; Rani Mega Putri (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine new technology used in science teaching and learning to support the implementation of the independent curriculum. The research method used is systematic literature review (SLR), namely researchers reviewing various journal articles that have been published from 2020-2023 via Google Scholar. From the research results, by following established research procedures, 7 journal articles were reviewed. From the results of the review, it was found that the technology that can be utilized in science teaching and learning is multimedia/video assisted learning; Learning with the help of digital games; Learning assisted by computer simulation; Comic-assisted learning; Learning using the Google Classroom platform; and Learning using Web 2.0. Meanwhile, the appropriate devices used in science teaching and learning to achieve predetermined learning objectives are Cell Phones/Android, PDAs, Tablets, Laptops, e-books, and iPods. To optimize the use of technology in science classes, teachers should use collaborative learning approaches, inquiry learning, project-based learning, problem-based learning, game-based learning, and flipped classroom learning. For game-assisted learning, teachers must create good learning scenarios and choose the right games according to learning objectives.